2019
DOI: 10.23917/mijeb.v2i1.9383
|View full text |Cite
|
Sign up to set email alerts
|

The Distinction Between Sharia Market and Conventional Market: A Study on Indonesia Stock Exchange

Abstract: The  present  study  investigates  the  differences between Islamic Economic System and Conventional Economic System that supposedly lead to the differences between sharia market and conventional market. Through bivariate and multivariate analysis, regression, correlation, and determination tests were carried out to identify the effect of conventional market on sharia market. Analysis was done based on the data of Indonesia Stock Exchange from December 2006 to May 2017, The data consisted of Jakarta Stock Exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The conventional market disregards the "halal-haram" aspects [5] and does not align with the principles of Shariah or Islamic law. It uses the concept of interest containing usury, and speculative/manipulative transactions (Nurhayadi and Rito, 2019). Contrarily, the Islamic market follows the principles of Shariah or Islamic law, prohibiting the "halal-haram" aspects.…”
Section: Literature Review 21 Conventional and Islamic Marketsmentioning
confidence: 99%
“…The conventional market disregards the "halal-haram" aspects [5] and does not align with the principles of Shariah or Islamic law. It uses the concept of interest containing usury, and speculative/manipulative transactions (Nurhayadi and Rito, 2019). Contrarily, the Islamic market follows the principles of Shariah or Islamic law, prohibiting the "halal-haram" aspects.…”
Section: Literature Review 21 Conventional and Islamic Marketsmentioning
confidence: 99%
“…Studies highlight differences in the response of Sharia Stock Markets to macroeconomic variables such as inflation and interest rates. Some research suggests that Sharia Stock Markets may exhibit different reactions to inflation compared to conventional stock markets, possibly due to the prohibition of prohibited goods and an aversion to excessive risktaking in Islamic financial principles (Indarwati & Widarjono, 2021;Nurhayadi & Rito, 2019). Moreover, the impact of inflation on the volatility of Sharia Stock Markets in developed and developing countries has been explored, with findings suggesting that Islamic stock indices may demonstrate greater resilience to financial crises and unique characteristics that differentiate them from conventional stock markets (Sampurna & Maronrong, 2019).…”
Section: Inflation and Sharia Stock Marketmentioning
confidence: 99%
“…They assume the Jakarta Islamic Index (JII) and the Indonesia Sharia Stock Index (ISSI) as a representation of the sharia market and the Jakarta Composite Index (IHSG) and the Jakarta Stock Exchange Liquid (LQ45) as a representation of the conventional market. Subsequent research by Rito;Azizah, 2018) revealed that the assumption that the IHSG and LQ45 represent conventional markets, because the IHSG and LQ45 are also dominant Islamic issuers. Their research specifically found that Islamic stocks are better than conventional stocks.…”
Section: Introductionmentioning
confidence: 99%